Tracking nest-rescued green sea turtles in oceanic currents sheds light on eastern Caribbean “lost years” - Levenson, J. Jacob; Cooper, Robert; Weissman, Amelia; Bell, Desirée; Smith, Jamison; Harris, Marcella (Frontiers in Amphibian and Reptile Science, 2024)
Although sea turtles are well-studied charismatic marine species, little is known about the juvenile stage, especially the oceanic phase between hatching on their natal beaches and their adult lives. To collect data on these “lost years,” six juvenile green turtles were equipped with satellite tags, released from southwestern Dominica in the eastern Caribbean, and tracked for up to 3 months. Mapping turtle movement to ocean currents reveals that juvenile green turtles spent most of their travel time within the Caribbean Sea, passively riding the prevailing currents before actively directing themselves toward distant coastal waters. Half of the tagged turtles traveled to coastal foraging grounds off of Colombia and Venezuela, while one traveled north past Puerto Rico. These findings provide novel data for the movements of juvenile green turtles hatched in the Eastern Caribbean region.